2012
DOI: 10.1371/journal.pone.0051088
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity of Paternal and Maternal Non-Parental Female Relatives of Homosexual and Heterosexual Men

Abstract: A variety of social, developmental, biological and genetic factors influence sexual orientation in males. Thus, several hypotheses have attempted to explain the sustenance of genetic factors that influence male homosexuality, despite decreased fecundity within the homosexuals. Kin selection, the existence of maternal effects and two forms of balancing selection, sexually antagonistic selection and overdominance, have been proposed as compensatory mechanisms for reduced homosexual fecundity. Here, we suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 61 publications
3
25
1
1
Order By: Relevance
“…If the Samoan population is relatively free of susceptibility to anomalous reproductive patterns compared to Western populations, then the study by indicates that male androphilia is associated with elevated reproductive output in both the maternal and paternal lines. This is not the case for some of the research that has been presented from certain Western populations (e.g., Camperio Ciani et al, 2004;Iemmola & Camperio Ciani, 2009;Camperio Ciani & Pellizzari, 2012;Rahman, Collins, Morrison, Orrells, Cadinouche, Greenfield et al, 2008). On the basis of our Samoan research, it seems reasonable to argue that sexually antagonistic genetic factors may be present on the autosomal chromosomes because androphilic males share genetic factors on these chromosomes with both paternal and maternal relatives.…”
Section: Tests Of the Sexually Antagonistic Gene Hypothesis In Samoanmentioning
confidence: 68%
“…If the Samoan population is relatively free of susceptibility to anomalous reproductive patterns compared to Western populations, then the study by indicates that male androphilia is associated with elevated reproductive output in both the maternal and paternal lines. This is not the case for some of the research that has been presented from certain Western populations (e.g., Camperio Ciani et al, 2004;Iemmola & Camperio Ciani, 2009;Camperio Ciani & Pellizzari, 2012;Rahman, Collins, Morrison, Orrells, Cadinouche, Greenfield et al, 2008). On the basis of our Samoan research, it seems reasonable to argue that sexually antagonistic genetic factors may be present on the autosomal chromosomes because androphilic males share genetic factors on these chromosomes with both paternal and maternal relatives.…”
Section: Tests Of the Sexually Antagonistic Gene Hypothesis In Samoanmentioning
confidence: 68%
“…Homosexual and heterosexual subjects are compared with regard to the number of offspring produced by various classes of relatives, for example, mothers, grandmothers, sisters, brothers, aunts, uncles and cousins. Several such studies have found evidence of greater fecundity in the relatives of homosexual subjects, but they differ in finding this primarily on the mother's side [6][7][8][41][42][43], on the father's side [36,38] or about equally on both sides [44,45]. These studies might be useful for investigating patterns of transmission of fecundity-promoting genes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Sexually antagonistic mechanisms propose that alleles inducing male homosexuality may increase female fitness but be detrimental (or indifferent) to male fecundity. This mechanism is supported by two mathematical models [14,24] and data showing that female maternal relatives (or both maternal and paternal line relatives) of homosexual men have increased fecundity compared with relatives of heterosexual men [11–13,25]. These models and behavioral data, such as fecundity rates, are only available for hypotheses regarding male homosexuality.…”
Section: Introductionmentioning
confidence: 95%